Toughening of poly(lactic acid) without sacrificing stiffness and strength by melt-blending with polyamide 11 and selective localization of halloysite nanotubes - B. J. Rashmi; K. Prashantha; M-F. Lacrampe; P. Krawczak (eXPRESS Polymer Letters)
This paper aims at improving the mechanical behavior of biobased brittle amorphous polylactide (PLA) by extrusion melt-blending with biobased semi-crystalline polyamide 11 (PA11) and addition of halloysite nanotubes (HNT). The morphological analysis of the PLA/PA11/HNT blends shows a strong interface between the two polymeric phases due to hydrogen bonding, and the migration of HNTs towards PA11 phase inducing their selective localization in one of the polymeric phases of the blend. A ‘salami-like’ structure is formed revealing a HNTs-rich tubular-like (fibrillar) PA11 phase. Moreover, HNTs localized in the dispersed phase act as nucleating agents for PA11. Compared to neat PLA, this leads to a remarkable improvement in tensile and impact properties (elongation at break is multiplied by a factor 43, impact strength by 2, whereas tensile strength and stiffness are almost unchanged). The toughening mechanism is discussed based on the combined effect of resistance to crack propagation and nanotubes load bearing capacity due to the existence of the fibrillar structure. Thus, blending brittle PLA with PA11 and HNT nanotubes results in tailor-made PLA-based compounds with enhanced ductility without sacrificing stiffness and strength.